Major risk factors that are potential for infertility among male semester 3 and 5 medical students, Faculty of Medicine, Udayana University year 2017 - Yashni Subramaniam; Nyoman Mangku Karmaya (Intisari Sains Medis, 2019)
Introduction: A couple being unable to get pregnant result out of unprotected sex and have been trying for one year is defined as the inability to conceive or infertile. Other reasons can be due to the male lifestyle itself, for example obesity, alcohol consumption and also smoking. This study aims to look for various things that might be risk factors for infertility in male students of semester III and V, in the Faculty of Medicine of Udayana University in 2017.Method: This study used a descriptive cross-sectional design carried out during the 2017 period using the questionnaire given to respondents, a total of 116 male respondents in this study. Identification of lifestyle that can be a risk factor for infertility was assessed in all respondent.Result: Through this research, it can be known that lifestyle risk factors that cause infertility are using a laptop on the lap for hours (29.3%), injury in groin area (14,%), alcoholism (11.2%), continuous fast food consumption (12.1%), and obesity (6.9%), and active smoker (1.7%). In the other side of the person still doing a sedentary lifestyle and low physical activity.Conclusion: Sedentary lifestyles with low physical activity are common lifestyle finding among medical students so that this can be a lifestyle that becomes a risk factor for the onset of infertility.